The Agenda for Gamers: Propaganda and Inclusion in Computer Games - Tatyana A. Aseeva (RUDN Journal of Political Science)
The issue of propaganda of ideas and meanings in computer games is in the focus of researchers’ attention. However, the integration of social agendas and minority values into the gameplay is becoming more ambitious, which requires careful analysis. Studying this phenomenon, determining its causes and possible consequences is of interest for political science analysis, as it allows us to assess the prospects for using gaming platforms to form an agenda for the gaming environment, broadcast and incorporate certain ideas and views in milder forms, as opposed to propaganda. The communicative approach of H.M. McLuhan was used to understand the essence of computer games and their significance in the life of society. The agenda theory proposed by M. McCombs and D. Shaw made it possible to identify the reasons for the appearance of “agendas” in computer games and analyze the communication channels through which issues of representation of minorities and their values are actualized for the gaming community. It has been found that the use of computer games for the purpose of openly promoting specific ideas, attitudes or actions to a mass audience is ineffective, because in the absence of audience interest, such an impact meets resistance, which manifests itself in the rejection of gaming products. To broadcast specific ideas, it is necessary either to rely on existing patterns formed not only under the influence of gaming experience, or to do so at such a high ideological and technological level that the gaming community would not reject this product. At the same time, the degree of influence on the player’s consciousness will be significantly lower. Unlike narrowly focused propaganda games, caused by the attitudes of individual Western countries, the DEI agenda has left few people indifferent in the global gaming community. There are ongoing discussions on this issue online, reflecting a conflict of values.